1865-66 Ala. Laws 7, ch. 1 (Feb. 22, 1866) - (:unkn) unknown (General Publisher, 1866)
Imposed an annual tax of two dollars on each person who is not a regular dealer but in possession of pistols and revolvers. Imposed an annual tax of three dollars on each person who is not a regular dealer but in possession of bowie knives or knives of like description.
--
Keywords: TAX - PROPERTY OR SALES